MINFLUX dissects the unimpeded walking of kinesin-1 - Wolff, Jan Otto; Scheiderer, Jan Lukas; Engelhardt, Tobias; Engelhardt, Johann; Matthias, Jessica; Hell, Stefan (Science, 2023)
We introduce an interferometric MINFLUX microscope that records protein movements with up to 1.7 nanometer per millisecond spatiotemporal precision. Such precision has previously required attaching disproportionately large beads to the protein, but MINFLUX requires the detection of only about 20 photons from an approximately 1-nanometer-sized fluorophore. Therefore, we were able to study the stepping of the motor protein kinesin-1 on microtubules at up to physiological adenosine-5′-triphosphate (ATP) concentrations. We uncovered rotations of the stalk and the heads of load-free kinesin during stepping and showed that ATP is taken up with a single head bound to the microtubule and that ATP hydrolysis occurs when both heads are bound. Our results show that MINFLUX quantifies (sub)millisecond conformational changes of proteins with minimal disturbance.
Gesehen am 13.03.2023